ANALYSIS OF PASSENGER TERMINAL SERVICE QUALITY LEVEL AT BANYUWANGI AIRPORT - Nugroho, Deden; Oetomo, Wateno; Marleno, Risma (International Journal of Social Service and Research, 2025)
Banyuwangi Airport has become an important air transportation facility in East Java, playing a strategic role as a gateway to leading tourist areas. This study aims to identify the current level of service quality of the passenger terminal at the airport, understand the factors that influence its performance, and develop evidence-based recommendations to improve service quality. A systematic research design was implemented, encompassing stages from problem identification to data analysis and report preparation. The primary objective was to identify aspects of terminal services needing improvement to enhance user satisfaction, guided by initial observations and literature reviews. The analysis of hierarchical processes (AHP) method was employed for data analysis, focusing on assessing criteria weights through pairwise comparisons to generate improvement recommendations. The results indicate that passenger satisfaction varies significantly across different types of facilities. Several concrete steps and strategic recommendations are proposed to enhance service quality and address the identified gaps.